Nanoparticles induced cuproptosis to enhance antitumor immunotherapy - Wen Deng; Zichen Zhong; Haojie Shang; Yonghua Tong; Qiu Huang; Yu He; Jian Wu; Xiaozhuo Ba; Zhiqiang Chen; Yuan Chen; Kun Tang (Journal of Nanobiotechnology)
Abstract Immunotherapy is a highly promising cancer treatment method. However, it is limited by low immunogenicity and an immunosuppressive microenvironment, which could be relieved by immunogenic cell death (ICD). Currently, effective ICD is primarily achieved through apoptosis induction, but tumor cells' resistance to apoptosis limits its antitumor efficacy. Therefore, developing new cell death modalities with high immunogenicity for cancer immunotherapy is of great significance. Cuproptosis, a newly discovered form of programmed cell death, can effectively circumvent tumor cells' resistance to apoptosis. Various Cu ionophores have been studied as anticancer drugs to promote cuproptosis, but the lack of tumor specificity remains one of the major challenges in this field. In contrast, nanoparticles tend to preferentially accumulate in tumor tissues due to the enhanced permeability and retention (EPR) effect, and they can be surface-modified to achieve active tumor targeting capabilities. Recently, many unique physicochemical properties of nanoparticles have been designed as nano-inducers of cuproptosis, successfully enhancing immunotherapy. Based on this, this review detailedly summarized various strategies and applications of nanoparticles-induced cuproptosis in tumor cells. The role of Cu metabolism and homeostasis in tumorigenesis and development, the molecular mechanisms of cuproptosis and different cuproptosis inducers with promising application prospects, as well as the interaction between cuproptosis and immunotherapy have also been reviewed. Finally, we presented the limitations and future prospects of cuproptosis nano-inducers, hoping to provide a new strategy to enhance antitumor immunotherapy. Graphical Abstract